4x+4(x+3)=36

Simple and best practice solution for 4x+4(x+3)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+4(x+3)=36 equation:


Simplifying
4x + 4(x + 3) = 36

Reorder the terms:
4x + 4(3 + x) = 36
4x + (3 * 4 + x * 4) = 36
4x + (12 + 4x) = 36

Reorder the terms:
12 + 4x + 4x = 36

Combine like terms: 4x + 4x = 8x
12 + 8x = 36

Solving
12 + 8x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 8x = 36 + -12

Combine like terms: 12 + -12 = 0
0 + 8x = 36 + -12
8x = 36 + -12

Combine like terms: 36 + -12 = 24
8x = 24

Divide each side by '8'.
x = 3

Simplifying
x = 3

See similar equations:

| 12x+9y=360 | | -20=5+7(y+9) | | 4.5x-40.5=13.5 | | 2a+5a-13=50 | | -2v+8=8+3v | | 27y-3y+6y=30 | | 6y-2=3 | | (6x+3)(x+5)=(2+x)(6+2x)-4 | | 3+6p=63 | | -6+5s=-71 | | -7+3y=-22 | | -6x-21=-141 | | 3X^2/20 | | 27=6d+9 | | 8x+5y+3x-2y= | | 7+4s=15 | | 900/45= | | 6+0k=256 | | 9(k-93)=18 | | 6a-6=2a+10 | | (2/3)*36 | | 2k-15=3 | | -8(-5p+4)-6=-8p+10 | | 15u-9u=30 | | 4(3x+5)-6(3x-5)=11x+3(2x-7) | | 10y+10=5y+20 | | 18=24-3w | | 4=2v-10 | | 16+2u=56 | | 0.4x+0.96=2.96 | | X^2=7/4 | | -17/5= |

Equations solver categories